Anti-ultraviolet hardened coating for PC material and preparation method of anti-ultraviolet hardened coating

By constructing an anti-ultraviolet hardening coating composed of an internal connecting layer, an intermediate functional layer and an external protective layer on PC material, the problems of easy migration and precipitation and photodegradation of traditional coatings are solved, and the resistance to UV and mechanical properties are improved.

CN120484311APending Publication Date: 2025-08-15JIANGSU AOJINGJIA ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510746641.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-05
Publication Date
2025-08-15

AI Technical Summary

Technical Problem

The UV-resistant coating of existing PC materials has problems such as easy migration and precipitation of small molecules, narrow absorption bandwidth, and accelerated PC yellowing by its own photodegradation products, resulting in limited UV-resistant performance.

Method used

The anti-ultraviolet hardening coating consisting of an internal connecting layer, an intermediate functional layer and an external protective layer are used. The internal connecting layer is cross-linked with the surface of the PC material through an epoxy-containing silicone coupling agent. The intermediate functional layer contains ZnO-SiO2 nanoparticles, benzotriazole derivatives and modified polyurethane acrylate. The external protective layer contains a composite of fluorine-modified nanodiamond and photocured silicone resin.

Benefits of technology

It enhances the UV resistance and mechanical properties of PC materials, inhibits yellowing, and improves the adhesion and light transmittance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005436170950000091
    Figure BDA0005436170950000091
  • Figure BDA0005436170950000101
    Figure BDA0005436170950000101
Patent Text Reader

Abstract

The invention discloses an anti-ultraviolet hardened coating for a PC material and a preparation method of the anti-ultraviolet hardened coating, and relates to the technical field of coatings, the anti-ultraviolet hardened coating is composed of an internal connecting layer, a middle functional layer and an external protective layer, the internal connecting layer contains an epoxy group-containing siloxane coupling agent, and the internal connecting layer is covalently connected with hydroxyl after being subjected to surface plasma activation of the PC material to generate hydroxyl, so that the adhesive force of the coating is enhanced; the middle functional layer contains ZnO-S < 2 > nano particles, a benzotriazole derivative and modified polyurethane acrylate, the ZnO-S < 2 > nano particles are of a core-shell structure formed by coating ZnO with S < 2 >, the S < 2 > shell layer inhibits the photocatalytic activity of ZnO and improves the dispersity, and the benzotriazole derivative serves as an anti-ultraviolet functional component, so that the photocatalytic activity of ZnO is improved, and the photocatalytic activity of ZnO is improved. A disulfide bond and a Schiff base structure are introduced into modified polyurethane acrylate through modification preparation, the disulfide bond can inhibit free radical chain reaction and reversible fracture / recombination under mechanical stress, and the Schiff base structure can capture Fe < 3 + > / Cu < 2 + > generated by PC degradation and inhibit catalytic oxidation of metal ions, so that the anti-ultraviolet performance and mechanical performance of the material are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coatings, and in particular to an anti-ultraviolet hardening coating for PC materials and a preparation method thereof. Background Art

[0002] Polycarbonate (PC) is widely used in automotive lampshades, optical lenses, electronic displays, and other fields due to its high light transmittance (>90%) and strong impact resistance. However, the benzene rings and ester bonds in its molecular structure are susceptible to photo-Fries rearrangement under ultraviolet light (especially in the 280-400nm range), causing yellowing, a degradation of mechanical properties, and surface chalking, which severely limits its service life.

[0003] In the existing technology, the above problems can be circumvented by providing an anti-UV coating on the surface of the polycarbonate material. However, most traditional anti-UV coatings currently use hydroxyphenyl triazines, benzotriazoles and other materials as the main functional materials. However, they have problems such as easy migration and precipitation of small molecules, narrow absorption bandwidth, and accelerated yellowing of PC by their own photodegradation products, which greatly limits their anti-UV performance. Summary of the Invention

[0004] The purpose of the present invention is to provide an anti-ultraviolet hardening coating for PC material and a preparation method thereof, to solve the following technical problems:

[0005] How to improve the UV resistance of UV-resistant hardening coatings for PC materials.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] An anti-UV hardening coating for PC material comprises an internal connection layer, an intermediate functional layer and an external protective layer; the internal connection layer is formed by cross-linking an epoxy-containing siloxane coupling agent with the surface of the PC material; the intermediate functional layer contains ZnO-SiO2 nanoparticles, benzotriazole derivatives and modified polyurethane acrylate in a mass ratio of 15:8:60; and the external protective layer contains a composite of fluorine-modified nanodiamonds and light-curing silicone resin in a mass ratio of (0.5-2):95.

[0008] Preferably, the outer protective layer contains a composite of fluorine-modified nanodiamond and light-cured silicone resin in a mass ratio of 1:95.

[0009] Preferably, the light-curable silicone resin is mercaptosiloxane.

[0010] Preferably, the epoxy-containing siloxane coupling agent is 3-glycidyloxypropyltrimethoxysilane.

[0011] Preferably, the benzotriazole derivative is any one of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole (UV-P), 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole (UV-326), and 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole (UV-327).

[0012] Furthermore, the preparation method of the modified polyurethane acrylate is:

[0013] Step A1, dissolving 4-aminobenzenethiol, diacetone acrylamide, and diethylamine in anhydrous ethanol, stirring and reacting at 40° C. for 30 minutes to obtain reaction solution 1;

[0014] Step A2, adding polytetramethylene glycol and isophorone diisocyanate to the reaction solution 1, heating to 75° C. and reacting for 1 hour to obtain the reaction solution 2;

[0015] Step A3: naturally cool the reaction solution 2 to 60° C., then sequentially add hydroxyethyl acrylate and the catalyst, stirring and reacting for 30 minutes, and finally add FeCl 3 , stirring and reacting for 10 minutes to obtain modified polyurethane acrylate.

[0016] Furthermore, in step 1, the molar ratio of 4-aminothiophenol, diacetone acrylamide, and diethylamine is 10:20:(0.4-0.7), preferably 10:20:0.5.

[0017] Furthermore, in step A1, the mass ratio of the 4-aminothiophenol, diacetone acrylamide, and diethylamine to anhydrous ethanol is 1:(2-3), preferably 1:2.5.

[0018] Furthermore, in step A2, the weight ratio of the reaction solution 1, polytetramethylene ether glycol, and isophorone diisocyanate is 3:10:7.

[0019] Furthermore, in step A3, the molar ratio of the hydroxyethyl acrylate to the 4-aminothiophenol in step 1 is 1:1; and the molar ratio of the hydroxyethyl acrylate, the catalyst and FeCl3 is 10:0.1:0.05.

[0020] Furthermore, in step A3, the catalyst is dibutyltin dilaurate.

[0021] Based on this, a preferred method for preparing modified polyurethane acrylate is obtained, comprising the following steps:

[0022] Step a1: In a stirred tank, 4-aminothiophenol, diacetone acrylamide, and diethylamine were dissolved in anhydrous ethanol at a molar ratio of 10:20:0.5, where the amount of anhydrous ethanol was 2.5 times the weight of the solute, and stirred at 40° C. for 30 minutes to obtain a reaction solution 1;

[0023] Step a2, adding polytetramethylene ether glycol and isophorone diisocyanate to the reaction solution 1, wherein the weight ratio of the reaction solution 1, polytetramethylene ether glycol, and isophorone diisocyanate is 3:10:7, heating to 75° C. and stirring for 1 hour to obtain a reaction solution 2;

[0024] Step a3, naturally cooling the reaction solution 2 to 60°C, then adding hydroxyethyl acrylate and dibutyltin dilaurate in sequence and stirring and reacting for 30 minutes, and finally adding FeCl3 and stirring and reacting for 10 minutes, the molar ratio of hydroxyethyl acrylate to 4-aminothiophenol in step 1 is 1:1; the molar ratio of hydroxyethyl acrylate, catalyst and FeCl3 is 10:0.1:0.05; to obtain modified polyurethane acrylate.

[0025] Furthermore, the preparation method of the ZnO-SiO2 nanoparticles is:

[0026] Step B1, in an ultrasonic mixer, dissolving zinc nitrate and cetyltrimethylammonium bromide in an ethanol aqueous solution at a molar ratio of 1:0.05, wherein the amount of ethanol is 2 times the weight of the solute, and then adding urea in an amount twice the molar amount of zinc nitrate, and ultrasonically mixing to obtain a mixed solution 1;

[0027] Step B2, adding tetraethyl silicate in an amount of 0.3 times the molar amount of zinc nitrate dropwise to the mixed solution, and mixing by ultrasonication to obtain a mixed solution II;

[0028] Step B3: centrifuge the second mixed solution, collect the solid material, and vacuum dry it at 60° C. for 2 h to obtain ZnO-SiO2 nanoparticles.

[0029] Furthermore, the preparation method of the fluorine-modified nanodiamond is:

[0030] Step C1, dispersing nanodiamonds in tetrahydrofuran, then adding perfluorooctyl vinyl ether and benzophenone, the mass ratio of nanodiamonds, perfluorooctyl vinyl ether and benzophenone being 10:5:1; stirring and reacting under a nitrogen atmosphere for 10 minutes to obtain a reaction solution 1;

[0031] Step C2, irradiating the reaction solution with an ultraviolet lamp having a wavelength of 254 nm at a position 10 cm from the surface for 8 minutes to obtain a second reaction solution;

[0032] Step C3: centrifuge and wash the reaction solution 2, and then vacuum dry it at 60° C. for 2 h to obtain fluorine-modified nanodiamonds.

[0033] In a second aspect, the present invention further discloses a method for preparing the above-mentioned UV-resistant hardening coating for PC material, comprising the following steps:

[0034] Step 1: Plasma activate the surface of the PC substrate film, then spray 0.5 mol / L 3-glycidyloxypropyltrimethoxysilane ethanol solution, and let it stand at 80°C for 10 minutes to form an internal connection layer;

[0035] Step 2: Disperse ZnO-SiO2 nanoparticles, benzotriazole derivatives, modified polyurethane acrylate, and photoinitiator in a mixed solvent of butyl acetate / propylene glycol methyl ether acetate, ultrasonicate for 30 minutes, and then spin-coat the inner connecting layer to form a film. Let it stand at 60°C for 2 minutes to form an intermediate functional layer.

[0036] Step 3: Mix the fluorine-modified nanodiamond and the silicone resin and stir them evenly, then spray them on the middle functional layer and irradiate them with ultraviolet light for 90 seconds to obtain an outer protective layer.

[0037] Preferably, in step 1, the spraying thickness of the 3-glycidyloxypropyltrimethoxysilane ethanol solution is 8-12 μm, more preferably 10 μm.

[0038] Preferably, in step 2, the thickness of the spin coating film is 50-100 um, more preferably 80 um.

[0039] Preferably, in step three, the spraying thickness is 10-20 μm, more preferably 15 μm.

[0040] Beneficial effects of the present invention:

[0041] The anti-ultraviolet curing coating for PC material of the present invention is composed of an internal connecting layer, an intermediate functional layer and an external protective layer, wherein the internal connecting layer contains an epoxy-containing siloxane coupling agent, which is covalently connected after plasma activation on the surface of the PC material to enhance the adhesion of the coating; the intermediate functional layer contains ZnO-SiO2 nanoparticles, benzotriazole derivatives and modified polyurethane acrylate, wherein the ZnO-SiO2 nanoparticles are a core-shell structure formed by SiO2 coating ZnO, the SiO2 shell inhibits the photocatalytic activity of ZnO and improves the dispersibility, the benzotriazole derivative serves as an anti-ultraviolet functional component, and the modified polyurethane acrylate is prepared by introducing disulfide bonds and Schiff base structures, the disulfide bonds can inhibit free radical chain reactions and can reversibly break / reorganize under mechanical stress, and the Schiff base structure can capture Fe generated by PC degradation. 3+ / Cu 2+, inhibiting the catalytic oxidation of metal ions, thereby enhancing the material's UV resistance and mechanical properties; fluorine-modified nanodiamonds are introduced into the external protective layer to avoid the damage to the surface structure caused by acid oxidation treatment, while improving the mechanical strength and protecting the intermediate functional layer. DETAILED DESCRIPTION

[0042] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0043] Unless otherwise specified, the experimental methods in the following examples are conventional methods and were performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials and reagents used in the following examples, unless otherwise specified, were all commercially available.

[0044] Preparation Example 1

[0045] To prepare modified polyurethane acrylate, follow the following steps in sequence:

[0046] Step a1: In a stirrer, dissolve 125.19 g (1 mol) of 4-aminothiophenol, 338.44 g (2 mol) of diacetone acrylamide, and 3.66 g (0.05 mol) of diethylamine in 1168.25 g of anhydrous ethanol, and stir at 40° C. for 30 min to obtain a reaction solution 1;

[0047] Step a2, taking 1200 g of reaction solution 1 and transferring it to another stirrer, adding 4000 g of polytetramethylene ether glycol and 2800 g of isophorone diisocyanate, heating to 75 ° C and magnetically stirring for 1 hour to obtain reaction solution 2;

[0048] Step a3: The reaction solution 2 was naturally cooled to 60°C, and then 116.12g (1 mol) of hydroxyethyl acrylate and 63.15g (0.1 mol) of dibutyltin dilaurate were added in sequence and stirred for reaction for 30min. Finally, 8.11g (0.05mol) of FeCl3 was added and stirred for reaction for 10min to obtain modified polyurethane acrylate.

[0049] Repeat the above steps to prepare a sufficient amount of modified polyurethane acrylate.

[0050] Preparation Example 2

[0051] Preparation of ZnO-SiO2 nanoparticles is carried out in the following steps:

[0052] Step b1: In an ultrasonic stirrer, 189.39 g (1 mol) of zinc nitrate and 364.45 g (1 mol) of hexadecyltrimethylammonium bromide were dissolved in 1107.68 g of ethanol solution (V 乙醇 :V 水 =3:1), and then 240.24 g (2 mol) of urea was added, and the mixture was ultrasonically mixed at 50 Hz for 20 min to obtain a mixed solution 1;

[0053] Step b2, adding 22.158 g (0.3 mol) of tetraethyl silicate dropwise to the mixed solution, and mixing by ultrasonication at 50 Hz for 10 min to obtain a mixed solution II;

[0054] Step b3: centrifuge the second mixed solution, collect the solid material, transfer it to a vacuum dryer, and vacuum dry it at 60° C. for 2 h to obtain ZnO-SiO2 nanoparticles.

[0055] Repeat the above steps to obtain a sufficient amount of ZnO-SiO2 nanoparticles.

[0056] Preparation Example 3

[0057] The preparation of fluorine-modified nanodiamonds is carried out in the following steps:

[0058] Step c1: In a reaction kettle, 100 g of nanodiamond was dispersed in 1000 mL of tetrahydrofuran, and 20 g of perfluorooctyl vinyl ether and 10 g of benzophenone were added. The mixture was stirred under a nitrogen atmosphere for 10 min to obtain a reaction solution 1.

[0059] Step c2: Use ultraviolet light with a wavelength of 254 nm (10 mW / cm 2 ) irradiating the reaction solution at a distance of 10 cm from the surface for 8 min to obtain a second reaction solution;

[0060] Step c3: centrifuge and wash the second reaction solution, and then vacuum dry it at 60° C. for 2 h to obtain fluorine-modified nanodiamonds.

[0061] By repeating the above steps, a sufficient amount of fluorine-modified nanodiamonds can be prepared.

[0062] Example 1

[0063] To make a UV-resistant hardening coating for PC materials, follow the steps below:

[0064] Step 1: The surface of the PC substrate film (25 cm long, 15 cm wide, and 0.2 mm thick) was plasma activated (Ar / O2 = 4:1, 100 W, 5 min), and then sprayed with a 0.5 mol / L 3-glycidyloxypropyltrimethoxysilane ethanol solution to a thickness of 20 μm. The film was allowed to stand at 80°C for 10 min to form an internal connection layer.

[0065] Step 2: The ZnO-SiO2 nanoparticles of Preparation Example 2, UV-P, the modified polyurethane acrylate of Preparation Example 1, and the photoinitiator TPO are dispersed in a mixed solvent of butyl acetate / propylene glycol methyl ether acetate with a volume ratio of 7:3 in a molar ratio of 15:8:60:2, and ultrasonically treated at 40 Hz for 30 minutes. Then, a film is spin-coated on the surface of the internal connection layer to form a film with a thickness of 80 μm, and the film is allowed to stand at 60° C. for 2 minutes to form an intermediate functional layer;

[0066] Step 3: Mix the fluorine-modified nanodiamond and mercaptosiloxane in a mass ratio of 1:95 and stir evenly, then spray them on the middle functional layer with a spray thickness of 15 μm and use ultraviolet light with a wavelength of 365 nm (800 mW / cm 2 ) irradiated for 90s to obtain an outer protective layer.

[0067] Through the above operation steps, an anti-ultraviolet curing coating is formed on the PC substrate film.

[0068] Example 2

[0069] The preparation of the anti-ultraviolet hardening coating for PC material is different from that in Example 1, except that in step 3, the mass ratio of the fluorine-modified nanodiamond and mercaptosiloxane is 0.5:95, and the other steps and conditions remain the same, and finally the anti-ultraviolet hardening coating is prepared on the PC substrate film.

[0070] Example 3

[0071] The preparation of the anti-ultraviolet hardening coating for PC material is different from that in Example 1, except that in step three, the mass ratio of the fluorine-modified nanodiamond and mercaptosiloxane is 2:95, and the other steps and conditions remain the same, and finally the anti-ultraviolet hardening coating is prepared on the PC substrate film.

[0072] Example 4

[0073] The preparation of the anti-ultraviolet hardening coating for PC material is different from that in Example 1, except that in step 2, UV-P is replaced by UV-326, and the other steps and conditions remain the same, and finally the anti-ultraviolet hardening coating is prepared on the PC substrate film.

[0074] Example 5

[0075] The preparation of the anti-ultraviolet hardening coating for PC material is different from Example 1 only in that in step 2, UV-P is replaced by UV-327, and the other steps and conditions remain the same, and finally the anti-ultraviolet hardening coating is prepared on the PC substrate film.

[0076] Comparative Example 1

[0077] To make a UV-resistant hardening coating for PC materials, follow the steps below:

[0078] Step 1: The ZnO-SiO2 nanoparticles of Preparation Example 2, UV-P, the modified polyurethane acrylate of Preparation Example 1, and the photoinitiator TPO are dispersed in a mixed solvent of butyl acetate / propylene glycol methyl ether acetate with a volume ratio of 7:3 in a molar ratio of 15:8:60:2, and ultrasonically treated at 40 Hz for 30 minutes. Then, the film is spin-coated on the surface of a PC substrate film (25 cm long, 15 cm wide, and 0.2 mm thick) to form a film with a thickness of 80 μm. The film is allowed to stand at 60°C for 2 minutes to form a functional layer.

[0079] Step 3: Mix the fluorine-modified nanodiamond and mercaptosiloxane in a mass ratio of 1:95 and stir evenly, then spray them on the middle functional layer with a spray thickness of 15 μm and use ultraviolet light with a wavelength of 365 nm (800 mW / cm 2 ) irradiated for 90s to obtain a protective layer.

[0080] Through the above operation steps, an anti-ultraviolet curing coating is formed on the PC substrate film.

[0081] Comparative Example 2

[0082] The preparation of the anti-ultraviolet hardening coating for PC material is different from that in Example 1, the only difference is that in step 2, the modified polyurethane acrylate is eliminated, and the other steps and conditions remain the same, and finally the anti-ultraviolet hardening coating is prepared on the PC substrate film.

[0083] Comparative Example 3

[0084] The preparation of the anti-ultraviolet hardening coating for PC material is different from that in Example 1, the only difference is that in step 2, the ZnO-SiO2 nanoparticles are eliminated, and the other steps and conditions remain the same, and finally the anti-ultraviolet hardening coating is prepared on the PC substrate film.

[0085] Comparative Example 4

[0086] The preparation of the anti-ultraviolet hardening coating for PC material is different from that in Example 1, except that in step 2, the modified polyurethane acrylate and ZnO-SiO2 nanoparticles are simultaneously eliminated, and the other steps and conditions remain the same, and finally the anti-ultraviolet hardening coating is prepared on the PC substrate film.

[0087] Comparative Example 5

[0088] The preparation of the anti-ultraviolet hardening coating for PC material is different from that in Example 1, the only difference is that in step 3, the fluorine-modified nanodiamond is eliminated, and the other steps and conditions remain the same, and finally the anti-ultraviolet hardening coating is prepared on the PC substrate film.

[0089] Comparative Example 6

[0090] The preparation of the anti-ultraviolet hardening coating for PC material is different from Example 1 only in that step 3 is eliminated, and the other steps and conditions remain the same, and finally the anti-ultraviolet hardening coating is prepared on the PC substrate film.

[0091] The performance tests of the UV-resistant hardened coatings prepared in Examples 1-5 and Comparative Examples 1-6 were performed, including hardness test, UV resistance test, light transmittance test and adhesion test. The test methods are as follows:

[0092] Hardness test: refer to ASTM D3363 standard method;

[0093] UV resistance test: refer to ASTM D2244 & ISO 7724 standard method;

[0094] Light transmittance: refer to ASTM D1003 standard method;

[0095] Adhesion: Refer to ASTM D3359 & ISO 2409 standard methods.

[0096] The test results are listed in Table 1, which is as follows:

[0097] Table 1

[0098]

[0099]

[0100] By analyzing the data in Table 1, it can be seen that compared with Comparative Examples 1-6, Examples 1-5 achieve better comprehensive performance in hardness, UV resistance, light transmittance and adhesion.

[0101] The above describes in detail several embodiments of the present invention. However, the above contents are only preferred embodiments of the present invention and should not be considered as limiting the scope of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.

Claims

1. An anti-ultraviolet curing coating for PC material, characterized in that: The invention comprises an internal connection layer, an intermediate functional layer and an external protective layer; the internal connection layer is formed by cross-linking an epoxy-containing siloxane coupling agent with the surface of a PC material; the intermediate functional layer contains ZnO-SiO2 nanoparticles, benzotriazole derivatives and modified polyurethane acrylate in a mass ratio of 15:8:60; the external protective layer contains a composite of fluorine-modified nanodiamonds and a light-cured silicone resin in a mass ratio of (0.5-2):

95.

2. The anti-ultraviolet curing coating for PC material according to claim 1, characterized in that: The preparation method of the modified polyurethane acrylate is: Step A1, dissolving 4-aminobenzenethiol, diacetone acrylamide, and diethylamine in anhydrous ethanol, stirring and reacting at 40° C. for 30 minutes to obtain reaction solution 1; Step A2, adding polytetramethylene glycol and isophorone diisocyanate to the reaction solution 1, heating to 75° C. and reacting for 1 hour to obtain the reaction solution 2; Step A3: naturally cool the reaction solution 2 to 60° C., then sequentially add hydroxyethyl acrylate and the catalyst, stirring and reacting for 30 minutes, and finally add FeCl 3 , stirring and reacting for 10 minutes to obtain modified polyurethane acrylate.

3. The anti-ultraviolet curing coating for PC material according to claim 2, characterized in that: In step 1, the molar ratio of 4-aminothiophenol, diacetone acrylamide and diethylamine is 10:20:(0.4-0.7).

4. The anti-ultraviolet curing coating for PC material according to claim 2, characterized in that: In step A1, the mass ratio of the 4-aminothiophenol, diacetone acrylamide, and diethylamine to anhydrous ethanol is 1:(2-3).

5. The anti-ultraviolet curing coating for PC material according to claim 2, characterized in that: In step A2, the weight ratio of the reaction solution 1, polytetramethylene ether glycol, and isophorone diisocyanate is 3:10:

7.

6. The anti-ultraviolet curing coating for PC material according to claim 2, characterized in that: In step A3, the molar ratio of the hydroxyethyl acrylate to the 4-aminothiophenol in step 1 is 1:1; the molar ratio of the hydroxyethyl acrylate, the catalyst and FeCl3 is 10:0.1:0.

05.

7. The anti-ultraviolet curing coating for PC material according to claim 1, characterized in that: The epoxy-containing siloxane coupling agent is 3-glycidyloxypropyltrimethoxysilane.

8. The anti-ultraviolet curing coating for PC material according to claim 1, characterized in that: The preparation method of the ZnO-SiO2 nanoparticles is as follows: Step B1, dissolving zinc nitrate and cetyltrimethylammonium bromide in an ethanol aqueous solution at a molar ratio of 1:0.05, adding urea in an amount twice the molar amount of the zinc nitrate, and mixing by ultrasonication to obtain a mixed solution 1; Step B2, adding tetraethyl silicate in an amount of 0.3 times the molar amount of zinc nitrate dropwise to the mixed solution, and mixing by ultrasonication to obtain a mixed solution II; Step B3: centrifuge the second mixed solution, collect the solid material, and vacuum dry it to obtain ZnO-SiO2 nanoparticles.

9. The anti-ultraviolet curing coating for PC material according to claim 1, characterized in that: The preparation method of the fluorine-modified nanodiamond is: Step C1, dispersing nanodiamonds in tetrahydrofuran, then adding perfluorooctyl vinyl ether and benzophenone, the mass ratio of nanodiamonds, perfluorooctyl vinyl ether and benzophenone being 10:5:1; stirring and reacting under a nitrogen atmosphere for 10 minutes to obtain a reaction solution 1; Step C2, irradiating the surface of the reaction solution with an ultraviolet lamp for 5-10 minutes to obtain a second reaction solution; Step C3: centrifuge and wash the second reaction solution, and then vacuum dry it to obtain fluorine-modified nanodiamonds.

10. A method for preparing an anti-ultraviolet curing coating for PC material according to any one of claims 1 to 9, characterized in that: The steps include: Step 1: Plasma activate the surface of the PC substrate film, then spray 0.5 mol / L 3-glycidyloxypropyltrimethoxysilane ethanol solution, and let it stand at 80°C for 10 minutes to form an internal connection layer; Step 2: Disperse ZnO-SiO2 nanoparticles, benzotriazole derivatives, modified polyurethane acrylate, and photoinitiator in a mixed solvent of butyl acetate / propylene glycol methyl ether acetate, ultrasonicate for 30 minutes, and then spin-coat the inner connecting layer to form a film. Let it stand at 60°C for 2 minutes to form an intermediate functional layer. Step 3: Mix the fluorine-modified nanodiamond and the silicone resin and stir them evenly, then spray them on the middle functional layer and irradiate them with ultraviolet light for 90 seconds to obtain an outer protective layer.